Calculations of tramway track capacity in the wide area networks - Molecki, Adam; Gąska, Damian (Transport, 2012)
The article shows a way of calculating the tram network capacity. A wide area network in Silesian Conurbation was used as an example (before and after planned modernization). Special attention was put on the traffic limiters like: single-track sections, stops, junctions, crossings with traffic lights, etc. Travel times and other characteristics were determined with the use of Monte Carlo method. In total, the capacity calculations of the tram network in Silesian Conurbation (divided into 74 sections) had taken into account: 131 crossings with traffic lights, 395 stops, 52 junctions, 51 single-track sections.First Published Online: 21 Dec 2012